ChemInform Abstract: Cross‐Coupling of Vinylethylene Carbonates with Arylboronic Acids Catalyzed by in situ Generated Palladium Nanoparticles in Water. Issue 46 (October 2016) - Mao, Yuxue; Zhai, Xing; Khan, Ajmal; Cheng, Jiong; Wu, Xue; Zhang, Yong Jian
Abstract: It is found that Pd(OAc)2 is reduced to form Pd‐nanoparticles by homo‐coupling of phenylboronic acid.